2014
DOI: 10.1111/jre.12199
|View full text |Cite
|
Sign up to set email alerts
|

Root coverage by coronally advanced flap with connective tissue graft and/or enamel matrix derivative: a meta‐analysis

Abstract: When combined with CAF, CTG contributed more in the increase of KTW, while EMD seemed helpful for wound healing by its potential in PPD reduction. However, further research is needed to clarify the effects on changes in RED and clinical attachment level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…To date, a robust body of evidence reports positive outcomes following the use of CAF, CAF + EMD and CAF + CTG in the treatment of localized gingival recession sites [7,9,11,12]. The consensus report of the AAP Regeneration Workshop [30] concluded that a subepithelial connective tissue graft (SCTG) represents the most effective treatment modality for Miller classes I and II single-tooth recession defects and provide the best root coverage outcome, but it is important to highlight the fact that also it has been observed that the incidence of adverse effects in gingival recession treatment, such as discomfort with or without pain, was also directly related to the donor sites of SCTG [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a robust body of evidence reports positive outcomes following the use of CAF, CAF + EMD and CAF + CTG in the treatment of localized gingival recession sites [7,9,11,12]. The consensus report of the AAP Regeneration Workshop [30] concluded that a subepithelial connective tissue graft (SCTG) represents the most effective treatment modality for Miller classes I and II single-tooth recession defects and provide the best root coverage outcome, but it is important to highlight the fact that also it has been observed that the incidence of adverse effects in gingival recession treatment, such as discomfort with or without pain, was also directly related to the donor sites of SCTG [31].…”
Section: Discussionmentioning
confidence: 99%
“…Pilloni and co-workers [11], suggested that the application of EMD enhanced significantly the extent of root coverage, the clinical attachment gain (CAL-gain), and the keratinized tissue (KT) augmentation. A recent meta-analysis on the effect of CTG and EMD in root coverage procedures concluded that when combined with CAF, CTG contributed more to increase KT width, whereas EMD seemed helpful for wound healing and resulted in a reduction of probing pocket depths [12].…”
Section: Introductionmentioning
confidence: 99%
“…; Cheng et al. ), for gain of keratinized tissue or for pontic sites (Gonzalez‐Martin et al. ; Sanz‐Martin et al.…”
mentioning
confidence: 99%
“…Soft tissue volume augmentation is usually carried out by the use of a subepithelial connective tissue graft (SCTG), a technique described in the 1980s (Langer & Calagna 1982). Many studies using SCTGs were performed for root coverage procedures (Cairo et al 2008;Cheng et al 2015), Date: Accepted 18 February 2017 To cite this article: Bienz SP, Jung RE, Sapata VM, H€ ammerle CHF, H€ usler J, Thoma DS. Volumetric changes and peri-implant health at implant sites with or without soft tissue grafting in the esthetic zone, a retrospective case-control study with a 5-year follow-up.…”
mentioning
confidence: 99%
“…According to many recent studies, the combination of EMD with CAF produces similar results as the combination of SCGT with CAF regarding the predictability of the treatment of gingival recessions [ 104 ] [ 105 ].…”
Section: Coronally Advanced Flap (Caf) Proceduresmentioning
confidence: 99%